(untitled) (Sains Humanika, 2011)
A few studies have indicated that use of Language Learning Strategy (LLS) was influenced by language learning motivation (Oxford dan Nyikos, 1989; Prokop, 1989; Okada et al. 1999). This paper reports on one study that sets out to investigate the employment of LLS by students of Arabic language based on level of language learning motivation. A total of 457 students from thirteen Religious Secondary Schools in Terengganu participated in this study. Data was collected by using a questionnaire adapted and modified from SILL (Oxford, 1990) and Language Learning Motivation part of the Affective Survey (Ehrman & Oxford, 1991). The results indicate that students were moderately motivated and language learners with higher level of motivation use LLS more frequently than less motivated language learners.